On the post-heat behavior of cement mortar containing mechanically modified ground coal bottom ash - Al Biajawi, Mohammad I.; Rahimah, Embong; Khairunisa, Muthusamy; Jabar, Haneen Abdel; Hilal, Nahla; Fadzli, Mohamed Nazri (Editorial Salud, Ciencia y Tecnologia, 2024)
Coal is widely recognized as a significant and essential fuel source due to its capacity to undergo combustion and produce heat in many different regions worldwide. Over the course of many decades, there has been a notable rise in power usage among individuals, thus resulting in an upsurge in the utilization of coal. The growth of mankind has a parallel rising trajectory with the utilization of cement in the building industry, as well as a corresponding rise in cement manufacturing. These two phenomena significantly contribute to the escalation of carbon dioxide (CO2) emissions and the improper disposal of coal ash, both of which pose significant environmental hazards. Coal-fired thermal power plants generate many waste products from industry, including coal-bottom ash (CBA), which may be effectively used in the production of mortar or concrete. This practice not only promotes the adoption of sustainable construction materials but also encourages the utilization of these wastes. In contrast, it is worth noting that cement manufacture yields a significant quantity of carbon dioxide emissions, so exerting a detrimental influence on the ecosystem. The reduction of environmental deterioration may be achieved by substituting cement with waste products. The substitution of Portland cement with reutilized coal combustion products has the potential to provide significant environmental and infrastructural advantages. This study presents an experimental investigation into the post-heat performance of cement mortars including ground coal bottom ash (CBA). To achieve this objective, an investigation was conducted to assess the strength qualities, residual strength, and mass losses of mortar specimens. These specimens comprised varying proportions (10 %, 20 %, 30 %, and 40 %) of CBA as a substitute for cement. To perform the heating procedure, samples were subjected to temperatures of 200°C, 400°C, and 600°C, which corresponded to room temperatures. The findings indicate that the use of ground CBA up to a proportion of 20 % yields mortar with the maximum value of compressive strength compared with the control sample. The use of a substantial amount of ground CBA has been shown to produce the most significant reduction in mass and decrease in strength when subjected to high temperatures. As a result, the residual strength of concrete experiences a decrease of 33,65 % when exposed to a temperature of 600°C in conventional concrete while for CBA in concrete decreases around 40,9 %. In general, the integration of ground CBA alternatives as an alternative to cement would result in a decrease in the need for the manufacture of cement and the environmental pollution associated with CBA discharge